Stalking and its Victims - Michailovič, Ilona (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English]Stalking is a complex social phenomenon that can take on many different forms. Stalking is a vicious, subtle and devastating crime, and the victims of stalking seem to suffer long-lasting consequences. A clear relationship emerges between the functioning and dissemination of gender stereotypes and stalking as a form of gender-based violence. In this study, the way in which stalking occurs is discussed, and the defendants’ and victims’ backgrounds are taken into account. This article discusses the criminalization of stalking, the reasons for stalking being criminalized and the sanctions applied for stalking.This article also addresses a range of issues that expressly substantiate a need for effective measures to be taken against stalking. The prevention of stalking is certainly a long process and cannot be done without the inspiration and activity from the state police, non-governmental organizations and the collaborations of victims, which are all essential if law enforcement agents are to gather useful information and understand the exact nature of the occurrences. Hence, more research needs to be conducted in this field. Additional attention, research and training are required to better understand the most effective responses to reduce the risk of recidivism.
Keywords: stalking,; victims and stalkers; criminalization of stalking; reaction and prevention